2020
DOI: 10.3390/ma13061318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gellan Gum/Tuna Skin Film in Guided Bone Regeneration in Artificial Bone Defect in Rabbit Calvaria

Abstract: It is necessary to prevent the invasion of soft tissue into bone defects for successful outcomes in guided bone regeneration (GBR). For this reason, many materials are used as protective barriers to bone defects. In this study, a gellan gum/tuna skin gelatin (GEL/TSG) film was prepared, and its effectiveness in bone regeneration was evaluated. The film exhibited average cell viability in vitro. Experimental bone defects were prepared in rabbit calvaria, and a bone graft procedure with beta-tricalcium phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Commercial membranes of bovine, porcine or equine xenogeneic collagen have a minimum integrity time of 30 days (ARAÚJO et al, 2021). This reinforces the candidacy of innovative fish biocomposites within the new generation of resorbable membranes for guided bone regeneration (GBR), which can already count on collagenous biopolymers with enzymatic degradation, with rare reports of apatite composites, reabsorbed by multinucleated foreign body giant cells (DANIELETTO-ZANNA et al, 2020;JUNG et al, 2020).…”
Section: In Vivo Biological Analysismentioning
confidence: 74%
See 1 more Smart Citation
“…Commercial membranes of bovine, porcine or equine xenogeneic collagen have a minimum integrity time of 30 days (ARAÚJO et al, 2021). This reinforces the candidacy of innovative fish biocomposites within the new generation of resorbable membranes for guided bone regeneration (GBR), which can already count on collagenous biopolymers with enzymatic degradation, with rare reports of apatite composites, reabsorbed by multinucleated foreign body giant cells (DANIELETTO-ZANNA et al, 2020;JUNG et al, 2020).…”
Section: In Vivo Biological Analysismentioning
confidence: 74%
“…G elatin has the ability to integrate well into any internal environment, whether animal or human, reducing chronic infl ammation (OGAWA et al, 2017). In the GBR of the calvaria of rabbits using tuna skin gelatin, Jung et al (2020) observed the preservation of the material's mechanical properties and inhibition of soft tissue invasion in the area for up to 4 weeks of the experiment. Sbricoli et al (2020) further reinforce the biomimicry of collagen membranes with the native type I molecule in periodontal connective tissue itself.…”
Section: In Vivo Biological Analysismentioning
confidence: 99%
“…This membrane is composed of collagen fibers and glycosaminoglycan, especially hyaluronic acid and chondroitin sulfate, and has a mechanical strength similar to that of commercial GBR collagen membranes, and thus, has the potential to be used for bone repair applications. Jung et al developed a gellan gum/tuna skin gelatin film and evaluated its effectiveness in rabbit calvaria bone regeneration combined with tri-calcium phosphate (TCP) implantation [29] . The repair effect was comparable with that of a commercial collagen membrane.…”
Section: Space-maintaining Materialsmentioning
confidence: 99%
“…6 These membranes must have certain fundamental characteristics, such as biocompatibility, stability, and adequate resorption time. 8 Grafts of porcine origin also have a similar degree of compatibility with grafts of human origin. 9 In GBR, success depends on the rate of resorption as well as the membrane's effectiveness as a barrier 8 to remain long enough for repair to occur.…”
Section: Introductionmentioning
confidence: 99%
“…8 Grafts of porcine origin also have a similar degree of compatibility with grafts of human origin. 9 In GBR, success depends on the rate of resorption as well as the membrane's effectiveness as a barrier 8 to remain long enough for repair to occur. 4 A wide variety of CMs are on the market, such as Bio-Gide (Geistlich Pharma AG, Wolhusen, Switzerland), which has high density and low porosity and is one of the most studied and utilized membranes in regeneration processes.…”
Section: Introductionmentioning
confidence: 99%